Karakter mulut dan variasi struktur gigi pada familia Bagridae yang tertangkap di Sungai Serayu Kabupaten Banyumas - Dian Bhagawati; Muh. Nadjmi Abulias; Adi Amuranto (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. The objective of the present study was to evaluate mouth character and tooth structure variations of Bagridae. The sampling was conducted on February to July 2012 at Serayu River Banyumas, the sampling was done four times with two week intervals using casting nets and gill nets. A total of three species Bagridae, namely Mystus gulio, Mystus nigriceps and Hemibagrus nemurus were recorded during the study. The results showed that there were no variation on mouth and dental structure among species. Thus, theese characters could not be used to discriminate species among these species.Keywords. Mouth character, tooth structure variations, Bagridae, River Serayu